Social control over the use of artificial intelligence systems by Public Administration - GONZÁLEZ-JULIANA, Álvaro; ILDEFONSO MENDONÇA , Maria Julia (Revista Jurídica Portucalense, 2025)
This article analyses the guiding principles of the use of artificial intelligence systems by the Public Administration: reserve of humanity, transparency and explainability. In particular, it is emphasised that access to algorithmic information backed by the LADA is an essential tool for carrying out social control over the use of artificial intelligence systems by the Public Administration. However, this access to algorithmic information must necessarily be accompanied by other documentation that describes the algorithms in a manner understandable to a human being.